Banks Specific Factor that Determinate the Profitability of Commercial Banks in Republic of North Macedonia: Array - Kosumi, Arbenita; Kosumi, Arbereshe (Acta Universitatis Danubius. Œconomica, 2021)
Banking sector plays an important role in economy and has significant impact on country’s economic growth. The purpose of this seminar paper is by utilizing empirically analyses to identify the key determinants of commercial banks’ profitability by case study, Republic of North Macedonia. Performance evaluation of commercial banks is grounded on the banks specific factors, exploiting data for the period 2012 -2018 for 13 commercial banks. For this purpose, the return on assets (ROA) is taken as a dependent variable, whereas capital adequacy (CAP), bank size (SIZE), credit risk (CR), revenue diversification (DIV), liquidity (L) and leverage (LEV) represent the independent variables. The regression analysis indicate that that commercial banks profitability in Republic of North Macedonia has been driven mainly by factors such as liquidity and size.